Polscy studenci w Wielkiej Brytanii i ich relacje z innymi Polakami = The Polish students in the United Kingdom and their relationships with other Poles - Łuczak, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the first part of the article, the author describes internal relationships among Polish emigrants who came to the United Kingdom in different historical periods. Characterizing the waves of migration indicates the complexity of Polish community in this country. In the second part of the article, the author presents the results of the research conducted among Polish students studying abroad and the way how they build their relationships with other members of the post-accession emigrants.
Keywords: studenci; Polacy za granicą; migracje; Wielka Brytania; students; Poles abroad; United Kingdom the; migration